Peningkatan Prestasi Belajar Siswa Pada Materi Tata Cara Sholat Sunah Melalui Pembelajaran Kontekstual - Lismiati (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2023)
National education functions to develop the next generation's abilities and skills to educate the nation's life. On the other hand, education is also expected to shape the character of students. The learning of Islamic religious education plays a role in the formation of student character as well as strengthening it. This study aims to improve student learning achievement in the matter of sunnah prayer procedures. The method in this research is Classroom Action Research (CAR). Researchers involved class IX students of SMP Negeri 1 Ngraho as research subjects. There are two cycles of CAR, each cycle consisting of planning, action, observation, and reflection. The results showed that learning through a contextual learning approach on sunnah prayer material could improve student achievement in class IX at SMP Negeri 1 Ngraho. This increase is shown from the results of student achievement scores on sunnah prayer material. The results of the average scores of student achievement before the action is 71.5; cycle I was 67.5; and cycle II was 79.5. The increase was also seen in the number of students declared complete with a score of > 75. Students declared complete before the action were 11 students; cycle I totaled 12 students; and cycle II totaled 28 students.